The future of luxury : how new luxury consumers are changing the marketing strategies of luxury fashion brands in the 21st century - Marxen, Malin Louisa (2023)
The rise in younger consumers due to the increase in spending power of Millennials, Generation Z, and Alpha has caused a shift in the luxury fashion industry. This research aims to investigate how luxury fashion brands can adapt their marketing strategies to successfully market to the new luxury consumer without losing the notion of exclusivity and luxury. Qualitative research, in the form of 5 interviews with marketing managers from luxury fashion brands (Gucci, Givenchy, Cartier, Ripa Ripa, and Zegna), was conducted to understand what is currently being done by main players in the industry, and what further steps might need to be taken. The findings suggest that luxury fashion brands must implement innovative solutions in the areas of sustainability, digitalization, and the customer retail experience in order to cater to the needs of new luxury consumers that were identified. Those needs included a strong desire for authentic sustainability and corporate responsibility, strong values and storytelling, as well as different product needs catered to their lifestyles and preferences. Additionally, it covers different strategic moves that brands can undertake to manage the luxury paradox, such as increasing prices, niche targeting and selective distribution.